Sediment release of nutrients and metals from two contrasting eutrophic California reservoirs under oxic, hypoxic and anoxic conditions - Defeo, Shelby; Beutel, Marc W.; Rodal-Morales, Naivy; Singer, Maia (Frontiers in Water, 2024)
Harmful algal blooms (HABs) degrade water quality through the production of potent toxins that pose critical management challenges, especially in water-scarce regions. This study examined how dissolved oxygen (DO) conditions at the sediment–water interface in reservoirs in Southern California, United States, affect internal nutrient loading, which can promote HABs through the release of nutrients and metals from sediment to overlaying water. Replicate 2-liter laboratory chamber experiments with minimally disturbed sediment and bottom water from shallow, hypereutrophic Lake Henshaw and moderately deep, meso-eutrophic Lake Wohlford were conducted at ~25°C for ~30 days under oxic (~ 8 mg/L DO), hypoxic (< 2 mg/L DO), and anoxic (0 mg/L DO) conditions. Anoxic conditions in Lake Henshaw chambers resulted in elevated fluxes of ammonia (366 mg-N/m2·d) and soluble reactive phosphorus (122 mg-P/m2·d) from sediment, while hypoxic conditions promoted the flux of manganese (14.9 mg/m2·d), iron (3.3 mg/m2·d), and some SRP (44 mg-P/m2·d). In Lake Wohlford, anoxic conditions resulted in sediment release of ammonia (82 mg-N/m2·d), soluble reactive phosphorus (67 mg-P/m2·d), manganese (24 mg/m2·d) and iron (1.9 mg/m2·d). Under oxic and hypoxic conditions, Lake Henshaw sediments exhibited some release of ammonia and soluble reactive phosphorus, while Lake Wohlford sediments exhibited negligible release. After adjusting for temperature, Lake Wohlford anoxic fluxes of ammonia and soluble reactive phosphorus appear consistent with other eutrophic systems (4–60 mg-N/m2⋅d and 10–53 mg-P/m2⋅d), while Lake Henshaw anoxic fluxes appear rather extreme. Results from Lake Henshaw suggest that different nitrogen to phosphorus ratios were released from sediment to overlaying water under hypoxia (very low ratio plus iron) versus anoxia (low ratio with high nutrient levels). This in turn could affect phytoplankton community composition and toxin production. Results are being used to help inform management strategies, such as dissolved oxygen or sediment amendments, to control internal nutrient loading and reduce HAB toxin production.